2021
DOI: 10.3390/beverages7010005
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Label Assessment Using Sensory and Biometric Analysis of Self-Isolating Panelists through Videoconference

Abstract: Label concepts, information, logos, figures, and colors of beverages are critical for consumer perception, preference, and purchase intention. This is especially relevant for new beverage products. During social isolation, many sensory laboratories were unable to provide services, making virtual sensory sessions relevant to studying different label concepts and design preferences among consumers. This study proposed a novel virtual sensory system to analyze coffee labels using videoconference, self-reported, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A total of n = 62 participants answered the questions for the sensory tasting of the six different yogurt samples. The participants included 47% self-identified Western consumers (29) and 53% Asian consumers (33), 68% females (42) and 32% males (20), with ages ranging from 21 to 58 years. The Western consumers were mainly Australian (14), European (8), North/South American (3) and Latin (4), and the Asian consumers were mainly Chinese (19), Indian/Sri Lankan/Bangladeshi (7), Korean (2), Filipino (1), Persian (1), Vietnamese (2) and Malaysian (1).…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of n = 62 participants answered the questions for the sensory tasting of the six different yogurt samples. The participants included 47% self-identified Western consumers (29) and 53% Asian consumers (33), 68% females (42) and 32% males (20), with ages ranging from 21 to 58 years. The Western consumers were mainly Australian (14), European (8), North/South American (3) and Latin (4), and the Asian consumers were mainly Chinese (19), Indian/Sri Lankan/Bangladeshi (7), Korean (2), Filipino (1), Persian (1), Vietnamese (2) and Malaysian (1).…”
Section: Participantsmentioning
confidence: 99%
“…This makes it significantly important to understand the role or acceptance of the yogurts by different cultures using a cross-cultural sensory experiment [19]. There have been several studies involving various products, such as coffee labels [20], chocolate [21], beer [22] and artificial sweeteners [23], where a combination of implicit and explicit sensory methods have been successfully integrated together to assess the consumer acceptability. In the case of the study with coffee labels, the biometrics technology of facial expression recognition was also shown to be a reliable method for sensory evaluation [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further developments involve the assessment of multiple participants to record their biometrics simultaneously and optimize the sensory session time. , and subconscious responses such as Joy and Smile (Figure in the Poster as supplementary material) [1]. Study 2 showed that consumers had more positive emotions and higher perceived quality towards beers, with higher liking of foamrelated parameters.…”
mentioning
confidence: 94%
“…Some of these were that the Premium label was associated with perceived coffee strength, brand as the preferred area of interest (AOI), 😍, and valence and relaxed subconscious responses. On the other hand, the Everyday label was associated with pleasantness, colors as preferred AOI, 😀, 😋, 🤩, and subconscious responses such as Joy and Smile (Figure in the Poster as supplementary material) [1]. Study 2 showed that consumers had more positive emotions and higher perceived quality towards beers, with higher liking of foam-related parameters.…”
mentioning
confidence: 97%